Taxonomic diversity in the global wheat phyllosphere mycobiome – a meta analysis - Fischer, Marie Højmark; Rzepczynska, Agnieszka; Kjøller, Rasmus (Frontiers in Plant Science, 2025)
Wheat (Triticum aestivum L.) is a major crop grown on all continents. Due to environmental concerns, it is desirable to reduce the inputs of both chemical pesticides and inorganic fertilizers. However, yield reduction must be expected when switching to low-input systems. To mitigate such losses, the use of natural or introduced microbiomes may provide the key to maintaining sustainable yield. Phyllosphere fungi, both endophytic and phylloplane-associated, colonize aboveground plant structures, some of which have the potential to mitigate biotic and abiotic stressors. A first step toward realizing the potential of the wheat microbiome is to map the current knowledge on wheat phyllosphere fungi. This meta-analysis aims to map the diversity and abundance of fungal taxa associated with the wheat phyllosphere across global wheat-producing areas. To this end, we searched previous published literature and retrieved fungal community data from relevant studies. Retrieved studies included both culturing-based and metabarcoding amplicon sequence-based studies. We retrieved and analyzed 33 studies from five regions across the world, which differed greatly in their taxonomic composition. Across all regions, we found that while the majority of identified genera were unique to individual studies, some genera occurred across all five wheat growing regions, specifically Alternaria, Aspergillus, Bipolaris, Candida, Chaetomium, Cladosporium, Epicoccum, Fusarium, Nigrospora, Penicillium, Pyrenophora, Stemphylium and Trichoderma. Furthermore, we identified that while community composition differed between wheat growing regions, the identification method used was the most significant factor determining the depiction of community composition. We also highlight a lack of research in important wheat growing regions that are important for global wheat production. These considerations and other knowledge gaps are used to pinpoint future research.